2023
DOI: 10.1038/s41598-023-31630-8
|View full text |Cite
|
Sign up to set email alerts
|

A double-spiral maze and hi-resolution tracking pipeline to study dispersal by groups of minute insects

Abstract: Minute insects such as parasitic micro-wasps have high basic and applied importance for their widespread use as biocontrol agents. Their dispersal is a phenotype of particular interest. Classically, it is evaluated using field releases, but those are time consuming, costly, and their results highly variable, preventing high-throughput and repeatability. Alternatively, dispersal can be studied using small-scale assays, but those neglect important higher-scale processes. Consequently, proper evaluation of disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The development of innovative tracking methods should improve the spectrum of animals whose movements might be studied in future years (see e.g. Cointe et al, 2023). For the tiniest invertebrates however, the contribution of active movements to overall displacements is likely to strongly decrease compared to the contribution of passive phoretic movements, especially for dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…The development of innovative tracking methods should improve the spectrum of animals whose movements might be studied in future years (see e.g. Cointe et al, 2023). For the tiniest invertebrates however, the contribution of active movements to overall displacements is likely to strongly decrease compared to the contribution of passive phoretic movements, especially for dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, improving our understanding of how animals move and behave in various contexts may help to tackle critical conservation aims [17,18], including the need to stabilize or increase the numbers of small or declining populations [19,20], ensure the dispersal of biocontrol agents under various conditions [21,22] and control invasive or pest species [23,24]. For instance, a recent study has shown that combining biopesticides (i.e., essential oils) and biocontrol agents ( Trichogramma evanescens ) to mitigate pest species in agricultural fields may be counter-productive by altering biocontrol agents’ fitness and behavior and hence their efficiency [21].…”
Section: Motivation and Significancementioning
confidence: 99%